Explaining dividend policies in Argentina - Bebczuk, Ricardo Néstor (2004)
Dividend policy is central to the performance and valuation of listed companies, but the issue still remains scarcely investigated in emerging countries. The purpose of this paper is to study, for the first time, the determinants of the dividend policy of listed companies in Argentina over the 1996-2002 period. Although the modern theory stresses agency and other informational problems as the principal explanations of the so-called dividend puzzle, we will contend here that for many companies with highly concentrated ownership, a model of a sole owner-manager provides most (but not all) of the needed clues to answer the question as to why companies pay dividends in Argentina. Our main findings are that: (a) Bigger and more profitable firms without good investment opportunities pay more dividends; (b) Companies with more fluid access to debt pay more dividends; (c) Furthermore, riskier and more indebted firms prefer to pay lower dividends, and the same applies to foreign-owned firms; (d) ADR issuers disburse more dividends than other companies; and (e) Firms do not seem to care about maintaining stable payout ratios over time, but there is some inertia in that non-payers tend to stay that way and otherwise.